Optimization of target layer selection in shale gas horizontal wells - Peirong ZHAO (Shiyou shiyan dizhi, 2020)
Through several years of exploration and development practices, China has realized the commercial development of shale gas from the Upper Ordovician Wufeng and Lower Silurian Longmaxi formations in the Sichuan Basin and its periphery. It has been recognized that shale gas reservoirs are self-generating and self-preserving with low porosity and permeability, which can be identified as the "artificial gas reservoir" and its production is mainly controlled by geological and engineering factors. Geological factors determine the shale gas enrichment, and engineering factors play a major role in shale gas yield. The accurate identification of "sweet spots" and the optimization of target layer selection in horizontal wells are so significant that they decide the final production of each shale gas well. A case study of target layer selection in the Jiaoshiba block of Fuling Gas Field shows that detailed research is the basis for identifying the target window, and the integration of geological and engineering technologies is the key to accurately identify the target layers. According to the specific geological conditions in different regions, applying both geological and engineering knowledge to pinpoint the target layer is an important factor for the ultimate success of shale gas exploration and development.